REFORMULASI HUKUM TERHADAP HAK CIPTA ATAS MUSIK SEBAGAI OBJEK PELUNASAN UTANG MELALUI JAMINAN FIDUSIA - Subrianty, Daeli (Masalah-Masalah Hukum, 2024)
The percentage of active paid music streaming users globally has increased dramatically yearly. However, the increase in active music users in Indonesia is separate from the development of Music Copyright regulations in Indonesia. This doctrinal legal research uses is analyzed through a statutory and conceptual approach. Based on the research that has been conducted, the regulation of Music Copyright as an object of Fiduciary Guarantee in Indonesia has been regulated under several regulations. However, there are challenges and obstacles in implementing the music copyright guarantee as an object of the Fiduciary Guarantee. Therefore, realizing legal reformulation efforts against related rules can be a progressive solution to create a dynamic legal system that can keep up with developments that occur in society.